TINJAUAN YURIDIS MENGENAI KLAIM ASURANSI JIWA YANG TIDAK DIBAYARKAN OLEH ASURANSI JIWA BERSAMA BUMIPUTERA 1912: Juridical Review of Life Insurance Claims That Are Not Paid By Asuransi Jiwa Bersama Bumiputera 1912 - Khalisha Erfira Septianita; Suci Lestari (AMICUS CURIAE, 2024)
AJB Bumiputera 1912 does not pay the insurance claims of its policyholders, especially the policies belonging to Mrs. Marlindawati and Mr. Rudhi Mukhtar. The problem is how is the form of AJB Bumiputera 1912's responsibility for non-payment of insurance claims to its policyholders based on insurance law. The research method used is normative, descriptive-analytic in nature, the main data is secondary data supported by interviews, the method of collecting data is by means of literature studies and interviews, qualitative analysis and the method of drawing conclusions is by means of a deductive method. The conclusion of the research is that according to insurance law AJBB must be responsible based on Article 40 paragraph (1) POJK 69/2016, but because AJBB is in the form of a joint venture, Article 33 paragraph (5) AD AJBB regulates losses to be borne by the policyholder as well. Suggestion: AJBB to immediately resolve its liquidity problems and fulfill its obligations and its policyholders can use deliberations to reach a consensus, mediation and arbitration, and file for PKPU or bankruptcy.